SOCIAL IDENTITY AND DIGITAL NETWORKS: RELIGIOUS MODERATION PRACTICES OF MUHAMMADIYAH BRANCHES AND SUB-BRANCHES IN SURABAYA - Khoirul Anam; M. Febriyanto Firman Wijaya (SOSIOEDUKASI, 2026)
This study examines social identity and digital networks in the practice of religious moderation among Muhammadiyah branches and sub-branches in Surabaya, Indonesia. Employing a mixed methods approach that integrates Social Network Analysis (SNA) with qualitative interpretive methods, the study aims to map the digital network structure of the organization, analyze the role of key actors in disseminating moderation values, and develop a conceptual model of a digital religious moderation network. The findings reveal that the digital moderation ecosystem of Muhammadiyah Surabaya operates through three structured narrative layers—policy, production, and distribution—underpinned by five mutually reinforcing factors: visionary leadership, digital social capital, autonomous infrastructure, digital literacy culture, and a responsive community feedback system. Key actors identified through degree centrality and betweenness centrality analysis play a significant role as bridges between communities in the digital preaching network. The dynamic interaction of these factors gives rise to the Organic Digital Moderation Ecology Model (MEDO), a bottom-up framework that transcends the top-down approaches dominating existing literature, while offering new theoretical contributions to the fields of religious communication and social network studies.